Shade nets and substrates in seedling production of Annona squamosa L. in the Roraima Cerrado - Tadashi Sakazaki, Roberto (2019)
Sugar apple (Annona squamosa L.) is one of the most widely grown member of the Annonaceae family in several regions, but there is still a lack of agronomic data regarding the management of its initial growth stages under Cerrado conditions. The aim of the present study was to evaluate the production of Annona squamosa L. seedlings under different environmental conditions achieved by using shade nets (E1: ChromatiNet® Silver 50%; E2: ChromatiNet® red 50%; E3: ChromatiNet® red 35%; E4: ChromatiNet® Silver 35%) in combination with four different substrates (S1: soil + sand + chicken manure; S2: soil + sand + cattle manure; S3: soil + sand + cattle manure + chicken manure; S4: soil + sand + sheep manure). An experiment was set up using a completely randomized design with treatments in a split-plot arrangement, with four replicates and ten plants per experimental unit. Seedling growth parameters and quality indices were evaluated. The tested environments had higher local temperatures relative to the external environment, which had a negative effect on plant growth. Environment E2 resulted in the highest plant height and dry weight, but led to uneven growth among the evaluated plant parts. The substrate with sheep manure (S4) did not benefit seedling production. The best results for seedling growth and quality were obtained with substrates S2 (soil + sand + cattle manure) and S3 (soil + sand + cattle manure + chicken manure), which are therefore promising for Annona squamosa L. seedling production in the Roraima Cerrado.